Prediction model for identifying high-risk groups for overweight or obesity among Korean men in their 30s and 40s - Myeunghee Han (BMC, 2024)
Abstract Purpose This study was aimed to build a prediction model to identify high-risk groups for overweight or obesity among Korean men in their 30s and 40s. Methods This study analyzed data from 28,388 men aged 30-40 years, gathered in the 2022 Community Health Survey. Participants were categorized into two groups based on BMI: underweight/normal weight group and overweight/obese group. This study used chi-squared tests and independent t-tests to compare general and health-related characteristics. Moreover, a prediction model was developed using decision tree analysis, and its validity was verified through a split-sample test. Results The proportions of participants in the underweight /normal and overweight/obese groups were 50.4% and 49.6%, respectively. The group with the highest overweight/obesity rate at 60.6% had the characteristics of drinking more than 7 cups at a time, being married, and lacking sleep. On the other hand, the group with the lowest overweight or obesity rate (38.7%) had the characteristics of drinking less than 6 cups of alcohol at a time, getting enough sleep, and smoking less than 15 cigarettes. Conclusions The rate of overweight and obesity among Korean males in their 30s and 40s is significantly high. This study found that individuals who consume more than seven glasses of alcohol at a time, are married, and do not get enough sleep are at high risk of being overweight or obese. Therefore, it is essential to develop and implement targeted intervention programs for this high-risk group of Korean men in their 30s and 40s.